Characterization of an Anti-Dermatophyte Cream from ZatariamultifloraBoiss.: Characterization of a Zatariacream - Aghel, Nasrin; Moghimipour, Eskandar; Ameri, Abdolghani (Iranian Journal of Pharmaceutical Sciences, 2007)
Throughout the world, there has been an increasing incidence of fungal infections,and because of drug resistance and toxicity associated with long-term treatment withantifungal drugs search for new drugs to treat fungal infections is ongoing. The aimof this study was to evaluate the physicochemical properties and stability of creamscontaining different concentrations of Zataria multifloraextract as anti-dermatophytepreparations. First, the minimum inhibitory concentration (MIC) of methanolic extractof aerial parts of Z. multiflora was assayed against various dermatophytes by in vitrotube dilution technique (MIC=0.5%). To select the best cream formulation, onegeneral formula of cleansing cream was considered and then corrected. The best baseformula was chosen according to its monotonousness, straightness and externalattractiveness. Formulations containing 1, 2 or 3% of the plant extracts wereprepared. Finally, a cream containing 10% bees wax, 58.8% liquid paraffin, 1.2%hard paraffin, 5% spermaceti, 1% borax, 1.4% tween 80, 0.15% methyl paraben,0.15% lactic acid, 0.05% propyl paraben, 2%Zatariaextract and water was chosenas the best formulation. The final product was a W/O cream with suitable appearanceand desirable physicochemical stability.